1995
DOI: 10.1002/1097-0142(19951101)76:9<1545::aid-cncr2820760908>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Clonal changes in inflammatory pseudotumor of the lung. A case report

Abstract: Background. Pulmonary inflammatory pseudotumor, also known as plasma cell granuloma among many other names, is widely believed to be an inflammatory or reactive lesion rather than a neoplasm, although its pathogenesis is still controversial. Methods. Cytogenetic analysis was performed on a lung mass that showed typical clinical and pathologic features of inflammatory pseudotumor. Ultrastructural and immunohistochemical studies were performed in addition to routine histologic examination. Results. Cytogenetic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(43 citation statements)
references
References 18 publications
1
41
0
1
Order By: Relevance
“…The cytogenetic features of cases 1, 2, 6, and 11 have been described previously. 6,8,9 Cytogenetic banding analyses had not been performed in the remaining seven cases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytogenetic features of cases 1, 2, 6, and 11 have been described previously. 6,8,9 Cytogenetic banding analyses had not been performed in the remaining seven cases.…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7][8][9][10] Approximately 50% of soft-tissue IMT karyotypes contain clonal rearrangements of the chromosome 2 short arm, [5][6][7][8][9][10] and each of two cytogenetically characterized IMTs arising in bone contained rearrangements of the HMGIC region on chromosome band 12q15. 8 Recently, Griffin et al 10 showed that IMT 2p rearrangements fall within an ϳ100-kb region containing the ALK receptor tyrosinekinase locus, on chromosome band 2p23.…”
mentioning
confidence: 99%
“…Some consider IMT to be an immunological response to an infectious or noninfectious insult (31,32). Other researchers found that there was ectopic chromosomal rearrangements in the long arm of chromosome 2 and the short arm of chromosome 9, and confirmed that IMT was a monoclonal proliferation by genetic and molecular techniques (33)(34)(35)(36). In addition, approximately half of IMTs harbor a clonal cytogenetic aberration that activates the ALK-receptor tyrosine kinase gene at 2p23 (15,37).…”
Section: Discussionmentioning
confidence: 96%
“…It has been debated whether IMT is a tumor or inflammation, and also whether it is benign or malignant [1] . However, recent studies on cytogenetic abnormalities, such as rearrangements of the ALK gene on chromosome 2p23 [4,5] , clonal chromosome abnormalities [6][7][8] , and DNA aneuploidy [9] , and the role of oncogenic viruses [10,11] in the pathogenesis of IMT suggest that it is a true neoplasm. According to the current classification of the World Health Organization [12] , IMT is a neoplasm with a tendency for local recurrence and a very low rate of metastasis, and is histopathologically composed of myofi broblastic spindle cells, with inflammatory cell infiltrate of plasma cells, lymphocytes and eosinophils.…”
Section: Discussionmentioning
confidence: 99%